NaSbS2 thin film materials, NiO / NaSbS2 heterojunctions and their photoelectric detection applications
By using a mixed solvent of ethylenediamine and β-mercaptoethanol on a NiO substrate to dissolve sodium hydroxide, antimony oxide and sulfur sublimation, a high-quality pure phase cubic crystal NaSbS2 film was successfully grown and NiO/NaSbS2 was constructed. The heterojunction solves the problems of low symmetry and low photoelectric conversion efficiency of the NaSbS2 thin film crystal structure in the prior art, and achieves efficient self-powered photoelectric detection performance.
Patent Information
- Application Number
- CN202411433963.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The prior art is difficult to prepare high-quality NaSbS2 thin films, and their crystal structure is low, making it difficult to use as a photosensitive material for photodetectors, resulting in low photoelectric conversion efficiency.
Sodium hydroxide, antimony oxide, and sublimation sulfur were dissolved by a mixed solvent of ethylenediamine and β-mercaptoethanol. A pure phase cubic crystal NaSbS2 film was grown on the NiO substrate by solution spin coating or spraying, and NiO/NaSbS2 was constructed. Heterojunction forms high-quality photodetection devices.
The preparation of a highly symmetric cubic crystal NaSbS2 film has been achieved, with a band gap of 1.70 eV, with excellent self-powered photodetection performance and low dark current. It is suitable for photodetectors, solar cells and other devices.
Smart Images

Figure CN118969876B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new electronic materials and new devices, and specifically relates to a NaSbS2 thin film material, a NiO / NaSbS2 heterojunction and photoelectric detection applications thereof, which can show good application prospects of self-powered photoelectric detection. Background Art
[0002] Optoelectronic materials, as a class of electronic materials with photoelectric coupling response that can be used to make optoelectronic semiconductor functional devices and integrated circuits, have broad application prospects, such as photodetectors, solar cells, photodiodes, optoelectronic memory, etc. In these application fields, photodetectors are devices that can convert optical signals into electrical signals, and they have important applications in optical communications, drones, and aerospace. The optoelectronic materials in photodetectors have a very important impact on the performance of the device. Nowadays, many types of optoelectronic materials have been deeply studied, such as ZnO, InGaAs, graphene, perovskite, etc. Although these materials have advantages in certain aspects such as performance, cost, and environmental friendliness, there are still many problems in the modern ultra-high performance and miniaturized commercial application process. For example, in addition to outstanding optoelectronic properties such as good defect physics and long carrier diffusion length, halide perovskites also have mixed properties of ionic and covalent bonds, which enables low-cost solution processing. However, lead has always been the main component of all high-performance perovskite devices, which has caused toxicity issues during device manufacturing, deployment, and disposal. Another disadvantage is that perovskites usually degrade when exposed to moisture and high temperature. Therefore, there is an urgent need to find new high-efficiency and low-cost optoelectronic materials. The development of new optoelectronic materials is expected to help the next generation of photodetectors avoid some performance and process limitations of traditional optoelectronic semiconductor materials, and provide a practical solution for the development of the next generation of photodetectors.
[0003] Alkali metal sulfur compounds MPnQ2 (M = Na, K, Rb, Cs, Pn = Sb, Bi, Q = S, Se, Te) have attracted the attention of our team. The interaction between electropositive alkali metals and sulfides shows a large degree of ionic nature, while the electronegativity difference between VA elements and sulfur elements is small, which makes them have a large covalent bond. These materials not only have very ideal theoretical properties of photosensitive semiconductors and low toxicity, but also have mixed ionic and covalent bond properties, similar to halide perovskites, which cleverly make up for the shortcomings of halide perovskites.
[0004] NaSbS2 is a computationally screened, bandgap g =1.5~1.8 eV semiconductor thermoelectric material has a large light absorption coefficient in the visible light range (α=10 4 ~105 cm -1 ), has been shown to be a very effective solar energy absorption material, using NaSbS2 nanoparticles to achieve an efficiency of 3.18% in dye-sensitized solar cells. The three elements used in NaSbS2 materials are low-cost, abundant, and non-toxic, making NaSbS2 a potential environmentally friendly light absorption material for solar cells. As a member of the alkali metal sulfur compounds, NaSbS2 has excellent photostability and high chemical stability, and has high scientific research and application value as a photosensitive material for photodetectors.
[0005] The existing technology discloses "a method for preparing sodium thioantimonite nanomaterial" (publication number: CN109437298A). The method is a hydrothermal method, using ammonium sulfide and antimony sulfide to mix, adding sodium hydroxide after heating, stirring, centrifuging, and vacuum drying to obtain NaSbS2 nanopowder. However, from the XRD spectrum in the invention, it can be seen that the product obtained by the proposed preparation method is not pure phase, but there are many impurity diffraction peaks; in addition, the NaSbS2 obtained in the invention is a monoclinic phase (PDF#32-1039), and the crystal structure has low symmetry and is difficult to be used as a photosensitive material for photodetectors; the NaSbS2 product in the invention is in the form of powder, which is not suitable for photoelectric thin film devices. Generally, thin films have more advantages than powders in terms of performance, stability, and application fields, but it is relatively difficult to prepare high-quality thin films, especially the development of NaSbS2 thin films. In the existing literature, Tang Jiang et al. (Chinese Chemical Letters, 2017, 28(04): 881-887) dissolved Sb2S3 in ammonium sulfide and then added NaOH to form a NaSbS2 precursor solution. They used spray pyrolysis to prepare an n-type NaSbS2 thin film with a high symmetry cubic system (PDF#97-006-0285). However, the uneven, small-sized, and pinhole-shaped film morphology reported in this report limited its application in solar cells, and its photoelectric conversion efficiency was only 0.13%. Therefore, developing a new synthesis method for preparing NaSbS2 thin films, studying their photophysical properties, and effectively applying them to photoelectric detection devices are of great reference significance for the innovative development of optoelectronic functional devices. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention provides a NaSbS2 thin film material, a NiO / NaSbS2 heterojunction and its application in photoelectric detection, aiming to develop an optoelectronic material, obtain a pure cubic NaSbS2 phase, obtain a high-quality NaSbS2 thin film morphology and achieve excellent self-powered photoelectric detection performance. The present invention proposes a NaSbS2 thin layer material as a light-absorbing layer, a pure phase NaSbS2 thin film and a NiO substrate to form a heterojunction, and when it is applied to photoelectric detection, it has low dark current and self-powered photoelectric detection performance. Specifically, the present invention is implemented by the following technical solutions:
[0007] Firstly, the present invention provides a NaSbS2 thin film material, which adopts a mixed solvent of ethylenediamine and β-mercaptoethanol to dissolve sodium hydroxide, antimony oxide, and sublimed sulfur, and reacts at 50-70°C to obtain a NaSbS2 precursor solution, and then the NaSbS2 precursor solution is coated on a substrate by a solution spin coating method or a spray method to grow a pure phase NaSbS2 thin film material on the substrate.
[0008] Preferably, the volume ratio of ethylenediamine to β-mercaptoethanol is 2-3:0.4-0.8. Preferably, the mass ratio of sodium hydroxide to antimony oxide to sublimated sulfur is 0.05-0.06:0.12-0.15:0.15-0.18.
[0009] Furthermore, the present invention adopts a mixed solvent of ethylenediamine and β-mercaptoethanol to dissolve sodium hydroxide, antimony oxide, and sublimed sulfur, and reacts at 60°C to obtain a precursor solution of NaSbS2, and then grows a pure phase cubic NaSbS2 phase and film on a NiO substrate by a solution spin coating method, and the band gap is 1.70 eV. The film has excellent morphology, simple preparation process, and low raw material and preparation cost. Among them, the amount of sodium hydroxide, antimony oxide, and sublimed sulfur is 0.0528 g, 0.1443 g, and 0.16 g, respectively, and the amount of ethylenediamine and β-mercaptoethanol is 2.4 mL and 0.6 mL, respectively.
[0010] Secondly, the present invention also provides a NiO / NaSbS2 heterojunction film, which is a heterojunction formed by the above-mentioned NaSbS2 thin film material and the NiO thin film.
[0011] In addition, the method for preparing the NiO / NaSbS2 heterojunction film of the present invention is preferably to use a magnetron sputtering device to sputter a layer of NiO film on ITO to obtain ITO / NiO; then spin-coat a NaSbS2 precursor solution on ITO / NiO and anneal to obtain a NiO / NaSbS2 heterojunction film.
[0012] Thirdly, the present invention also provides the application of the above-mentioned NiO / NaSbS2 heterojunction film in semiconductor functional devices, and the semiconductor functional devices are photodetectors, solar cells, photoelectric storage devices or photodiodes.
[0013] Preferably, the NiO / NaSbS2 heterojunction film is more suitable for application in a photodetector, wherein the photodetector is mainly composed of an ITO substrate layer, a NiO / NaSbS2 heterojunction film layer and an aluminum metal electrode, wherein NiO is used as a hole transport layer of the photodetector, and the NaSbS2 material can be used as a photosensitive film light absorbing layer of the photodetector. Specifically, the application can be carried out using a method comprising the following steps:
[0014] 1) Cleaning the conductive glass substrate and magnetron sputtering a hole transport layer on the substrate;
[0015] 2) Solution-grown NaSbS2 thin film on the hole transport layer;
[0016] 3) Thermally evaporate aluminum electrodes on NaSbS2 thin films.
[0017] A self-powered photodetection device can be obtained by the above method.
[0018] Furthermore, the NiO / NaSbS2 heterojunction film is used in a photodetector application, which can adopt the following method steps:
[0019] Step 1: Sputtering NiO film
[0020] The cleaned ITO substrate was placed in a magnetron sputtering apparatus, and NiO was sputtered onto the ITO substrate in an argon atmosphere for 23-28 minutes to create ITO / NiO;
[0021] Step 2: Prepare NaSbS2 precursor solution
[0022] Weigh sodium hydroxide, antimony oxide, and sublimed sulfur into a beaker, and add ethylenediamine and β-mercaptoethanol to form a mixed solution. Stir the mixed solution in an oil bath at 60°C until it is completely dissolved to form a yellow solution.
[0023] Step 3: Preparation of NaSbS2 thin film
[0024] In a glove box filled with nitrogen, ITO / NiO was placed on a coating machine, and the prepared NaSbS2 precursor solution was spin-coated on ITO / NiO and annealed and cooled. This process was repeated three times to obtain an ITO / NiO / NaSbS2 composite laminate film.
[0025] Step 4: Electrode plating
[0026] A layer of aluminum electrode with a thickness of 80-120 nm is coated on the surface of the ITO / NiO / NaSbS2 composite laminate film by a thermal evaporation coating apparatus.
[0027] Preferably, in step 3, the coating machine is accelerated to 2000 rpm at an acceleration of 500 rad / s, rotated for 20 s, annealed on a hot stage at 450° C. for 5 minutes, cooled for 3 minutes, and repeated 3 times.
[0028] The present invention develops a mixed solvent of ethylenediamine and β-mercaptoethanol to dissolve sodium hydroxide, antimony oxide, and sublimed sulfur as a precursor solution for synthesizing NaSbS2, and adopts a solution spin coating method to grow a pure phase cubic system NaSbS2 film, whose band gap is 1.70eV. The film has a simple preparation process, low raw material and preparation costs, and forms a heterojunction with a NiO substrate prepared by a magnetron sputtering method, showing excellent self-powered photoelectric detection performance, providing new optoelectronic materials, new synthesis methods, and new application examples for research in the field of optoelectronic devices.
[0029] The beneficial effects of the present invention are:
[0030] 1) XRD characterization shows that the precursor solution of NaSbS2 prepared by the present invention can successfully grow a highly symmetric cubic NaSbS2 film on the NiO film after spin coating and heat treatment. The film has a simple preparation process and low raw material and preparation costs.
[0031] 2) The obtained NaSbS2 film has no impurities and its band gap is measured to be 1.70 eV, which is a narrow band gap semiconductor. The film has a flat and uniform morphology and forms a heterojunction with the NiO film, which can be used to construct photodetectors, solar cells, photoelectric storage devices, photodiodes, etc.
[0032] 3) The constructed ITO / NiO / NaSbS2 / Al photodetector exhibits a low dark current: 8.42×10 -4 A.cm -2 Under external bias, the three visible light wavelengths all exhibit semiconductor characteristic curves; while without external bias, the three visible light wavelengths all exhibit self-powered photodetection characteristic curves. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the structure of the ITO / NiO / NaSbS2 / Al self-powered photodetector device of the present invention.
[0034] Figure 2 This is the X-ray diffraction pattern of the NaSbS2 thin film prepared in Example 1 of the present invention.
[0035] Figure 3This is the absorption spectrum of the NaSbS2 thin film prepared in Example 1 of the present invention through ultraviolet-visible-near-infrared diffuse reflectance conversion.
[0036] Figure 4 This is a scanning electron microscope image of the NaSbS2 thin film prepared in Example 1 of the present invention.
[0037] Figure 5 This is the volt-ampere characteristic curve of the NaSbS2-based photodetector device prepared in Example 1 of the present invention under dark conditions.
[0038] Figure 6 The volt-ampere characteristic curves of the NaSbS2 photoelectric detection device prepared in Example 1 of the present invention under light of different wavelengths.
[0039] Figure 7 It characteristic curve of the NaSbS2 photoelectric detection device prepared in Example 1 of the present invention under light of different wavelengths.
[0040] Figure 8 Scanning electron microscope images of NaSbS2 thin films prepared in Example 2 of the present invention at (a) 350°C, (b) 400°C, (c) 450°C, and (d) 500°C.
[0041] Fig. 9 It characteristic curves of the NaSbS2-based photodetector device prepared in Example 2 of the present invention at (a) 350°C, (b) 400°C, (c) 450°C, and (d) 500°C under illumination of different wavelengths.
[0042] Fig.10 Scanning electron microscope images of NaSbS2 thin films prepared by the two-step annealing method in Example 3 of the present invention at (a) 230 ℃ / 350 ℃, (b) 230 ℃ / 400 ℃, (c) 230 ℃ / 450 ℃, and (d) 230 ℃ / 500 ℃.
[0043] Fig.11 It characteristic curves of the NaSbS2-based photodetector device prepared by the two-step annealing method in Example 3 of the present invention at (a) 230 ℃ / 350 ℃, (b) 230 ℃ / 400 ℃, (c) 230 ℃ / 450 ℃, and (d) 230 ℃ / 500 ℃ under illumination of different wavelengths. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. The specific implementation described here is only used to explain the present invention and is not used to limit the present invention.
[0045] Example 1
[0046] In this embodiment, an ITO / NiO / NaSbS2 / Al photodetector based on a NiO / NaSbS2 heterojunction is prepared according to the following steps:
[0047] Step 1: Sputtering NiO film
[0048] Take 2×1.5 cm 2 Then put the cut ITO into a beaker, pour in deionized water, and then use an ultrasonic cleaner to clean it for 5 minutes. Then pour out the deionized water and add acetone to ultrasonically clean it for 5 minutes, and finally use ethanol to ultrasonically clean it for 5 minutes. Finally, put it in an oven to dry the ITO. Put the cleaned ITO into a magnetron sputtering instrument, put in the purchased NiO target, and sputter for 25 minutes to form an ITO / NiO structure film.
[0049] Step 2: Prepare NaSbS2 precursor solution
[0050] Weigh 0.0528 g of sodium hydroxide, 0.1443 g of antimony oxide, and 0.16 g of sublimed sulfur into a beaker, add 2.4 mL of ethylenediamine and 0.6 mL of β-mercaptoethanol and mix evenly. Place the mixture on a magnetic stirrer and stir in an oil bath at 60°C until it is completely dissolved and a yellow solution is formed.
[0051] Step 3: Preparation of NaSbS2 thin film
[0052] Place ITO / NiO in an ozone cleaner for 15 min. Place ITO / NiO on a coater in a nitrogen-filled glove box, spin coat the prepared NaSbS2 solution on ITO / NiO with a pipette, accelerate to 2000 rpm at 500 rad / s, spin for 20 s, anneal on a hot plate at 450 °C for 5 min, cool for 3 min, repeat 3 times, and ITO / NiO / NaSbS2 laminated film is obtained.
[0053] Step 4: Electrode plating
[0054] A 100 nm thick aluminum electrode was coated on the surface of the ITO / NiO / NaSbS2 film using a thermal evaporation coating apparatus to obtain an ITO / NiO / NaSbS2 / Al photodetector.
[0055] Figure 1 This is a schematic diagram of the structure of the self-powered photodetector device of the present invention. NiO is used as the P-type hole transport layer, and NaSbS2 is used as the N-type light absorption layer.
[0056] Figure 2This is the X-ray diffraction pattern of the NaSbS2 thin film prepared in Example 1 of the present invention. It can be seen that the diffraction peaks at 26.7°, 30.9°, and 44.3° correspond to the diffraction peaks in cubic NaSbS2 (PDF#97-006-0285) in sequence, and no diffraction peaks of impurities are observed, indicating that a pure phase cubic NaSbS2 thin film is prepared.
[0057] Figure 3 The NaSbS2 film prepared in Example 1 of the present invention is subjected to UV-visible-near infrared diffuse reflectance test and converted absorption spectrum. The band gap of the NaSbS2 film is obtained to be 1.70 eV by converting the Kubelka-Munk formula and making a tangent to the absorption cutoff edge, that is, the photosensitivity range is within the visible light.
[0058] Figure 4 This is a scanning electron microscope image of the NaSbS2 film prepared in Example 1 of the present invention. The surface morphology of the NaSbS2 film is flat and uniform.
[0059] Figure 5 The volt-ampere characteristic curve of the photodetector device with the ITO / NiO / NaSbS2 / Al structure prepared in Example 1 of the present invention under dark conditions. The dark current density without bias is 8.42×10 -4 A.cm -2 .
[0060] Figure 6 The volt-ampere characteristic curve of the photoelectric detection device of the ITO / NiO / NaSbS2 / Al structure prepared in Example 1 of the present invention under different wavelengths of light. The photocurrent of the device is larger under 530 nm light.
[0061] Figure 7 It characteristic curves of the photodetector device of ITO / NiO / NaSbS2 / Al structure prepared in Example 1 of the present invention under different wavelengths of light. The device responds to 405 nm, 530 nm, and 625 nm wavelengths of light without bias, and the switching ratio is the largest under 530 nm wavelength light. The fast photocurrent response under 0V bias indicates that the device has self-powered characteristics.
[0062] Example 2
[0063] Compared with Example 1, after spin coating the NaSbS2 precursor solution, the single-step annealing temperature was changed within the adjustment range of 350°C to 500°C, and the performance of NaSbS2 films with different morphologies and ITO / NiO / NaSbS2 / Al structure photodetectors were obtained.
[0064] Step 1: Sputtering NiO film
[0065] Take 4 pieces of 2×1.5 cm 2 Then put the cut ITO into a beaker, pour in deionized water, and then use an ultrasonic cleaner to clean it for 5 minutes. Then pour out the deionized water and add acetone to ultrasonically clean it for 5 minutes, and finally use ethanol to ultrasonically clean it for 5 minutes. Finally, put it in an oven to dry the ITO. Put the cleaned ITO into a magnetron sputtering instrument, put in the purchased NiO target, and sputter for 25 minutes to form an ITO / NiO structure film.
[0066] Step 2: Prepare NaSbS2 precursor solution
[0067] Weigh 0.0528 g of sodium hydroxide, 0.1443 g of antimony oxide, and 0.16 g of sublimed sulfur into a beaker, add 2.4 mL of ethylenediamine and 0.6 mL of β-mercaptoethanol and mix evenly. Place the mixture on a magnetic stirrer and stir in an oil bath at 60°C until it is completely dissolved and a yellow solution is formed.
[0068] Step 3: Preparation of NaSbS2 thin film
[0069] Place 4 pieces of ITO / NiO in an ozone cleaner for 15 min. In a glove box filled with nitrogen, place ITO / NiO on a coater, use a pipette to spin coat the prepared NaSbS2 solution on ITO / NiO, accelerate to 2000 rpm at 500 rad / s, rotate for 20 s, then anneal the 4 pieces on a hot stage at 350 ℃, 400 ℃, 450 ℃, and 500 ℃ for 5 minutes, cool for 3 minutes, and repeat 3 times. That is, 4 NiO / NaSbS2 laminated films with different annealing temperatures are obtained.
[0070] Step 4: Electrode plating
[0071] A 100 nm thick aluminum electrode was coated on the surface of the ITO / NiO / NaSbS2 film using a thermal evaporation coating apparatus to obtain an ITO / NiO / NaSbS2 / Al photodetector.
[0072] Figure 8 Scanning electron microscope images of NaSbS2 films prepared in Example 2 of the present invention at (a) 350 ℃, (b) 400 ℃, (c) 450 ℃, and (d) 500 ℃. It can be seen from the figure that the grains of the NaSbS2 film annealed at 350 ℃ and 400 ℃ are smaller and have more holes; the grains of the NaSbS2 film annealed at 450 ℃ are larger, and the film is more dense and uniform; the grains of the NaSbS2 film annealed at 500 ℃ are similar to those formed at 400 ℃, but the excessively high temperature causes some grains to be destroyed.
[0073] Fig. 9 It characteristic curves of the NaSbS2-based photodetector device prepared in Example 2 of the present invention at (a) 350 ℃, (b) 400 ℃, (c) 450 ℃, and (d) 500 ℃ under different wavelengths of light. By comparison, it can be seen that the photodetectors annealed at four different temperatures have the largest light response under 530 nm wavelength light; however, smaller grains and larger holes are formed under 350 ℃ and 400 ℃ annealing, resulting in a lower light response, and due to the interface pyroelectric effect, it has two current spikes of different polarities; the grains produced under 450 ℃ annealing are larger and denser, resulting in a larger light response; and at 500 ℃, although the grains produced are larger, they are damaged to a certain extent, resulting in a lower light response.
[0074] Example 3
[0075] Compared with Example 1, after spin coating the NaSbS2 precursor solution, a two-step annealing method is used to obtain NaSbS2 thin films with different morphologies and ITO / NiO / NaSbS2 / Al structure photodetectors.
[0076] Step 1: Sputtering NiO film
[0077] Take 4 pieces of 2×1.5 cm 2 Then put the cut ITO into a beaker, pour in deionized water, and then use an ultrasonic cleaner to clean it for 5 minutes. Then pour out the deionized water and add acetone to ultrasonically clean it for 5 minutes, and finally use ethanol to ultrasonically clean it for 5 minutes. Finally, put it in an oven to dry the ITO. Put the cleaned ITO into a magnetron sputtering instrument, put in the purchased NiO target, and sputter for 25 minutes to form an ITO / NiO structure film.
[0078] Step 2: Prepare NaSbS2 precursor solution
[0079] Weigh 0.0528 g of sodium hydroxide, 0.1443 g of antimony oxide, and 0.16 g of sublimed sulfur into a beaker, add 2.4 mL of ethylenediamine and 0.6 mL of β-mercaptoethanol and mix evenly. Place the mixture on a magnetic stirrer and stir in an oil bath at 60°C until it is completely dissolved and a yellow solution is formed.
[0080] Step 3: Preparation of NaSbS2 thin film
[0081] Place 4 pieces of ITO / NiO in an ozone cleaner for 15 min. In a glove box filled with nitrogen, place ITO / NiO on a coater, use a pipette to spin coat the prepared NaSbS2 solution on ITO / NiO, accelerate to 2000 rpm at 500 rad / s, rotate for 20 s, anneal on a hot plate at 230 °C for 20 minutes, cool for 3 minutes, repeat 3 times, then anneal the 4 pieces on a hot plate at 350 °C, 400 °C, 450 °C, and 500 °C for 5 minutes. That is, 4 NiO / NaSbS2 laminated films formed by the two-step annealing method were obtained.
[0082] Step 4: Electrode plating
[0083] A 100 nm thick aluminum electrode was coated on the surface of the ITO / NiO / NaSbS2 film using a thermal evaporation coating apparatus to obtain an ITO / NiO / NaSbS2 / Al photodetector.
[0084] Fig.10 Scanning electron microscope images of NaSbS2 films prepared by the two-step annealing method at (a) 230 ℃ / 350 ℃, (b) 230 ℃ / 400 ℃, (c) 230 ℃ / 450 ℃, and (d) 230 ℃ / 500 ℃ in Example 3 of the present invention. It can be seen from the figure that the grains of the NaSbS2 film annealed at 230 ℃ / 350 ℃ and 230 ℃ / 400 ℃ are smaller and have more holes; the grains of the NaSbS2 film annealed at 230 ℃ / 450 ℃ are larger, and the film is more dense and uniform; the grains of the NaSbS2 film annealed at 230 ℃ / 500 ℃ are similar to those formed at 400 ℃, but the excessively high temperature causes some grains to be destroyed. Compared with Example 2, the grains formed by the two-step annealing method are smaller than those formed by the direct annealing method.
[0085] Fig.11It characteristic curves of NaSbS2 photodetector devices prepared by two-step annealing method (a) 230 ℃ / 350 ℃, (b) 230 ℃ / 400 ℃, (c) 230 ℃ / 450 ℃, and (d) 230 ℃ / 500 ℃ under different wavelengths of light. By comparison, it can be seen that the photodetectors annealed at four different temperatures have the largest light response under 530 nm wavelength light; however, smaller grains and larger holes are formed under 230 ℃ / 350 ℃ and 230 ℃ / 400 ℃ annealing, resulting in lower light response; the grains produced under 230 ℃ / 450 ℃ annealing are larger and denser, making its light response larger; and at 230 ℃ / 500 ℃, although the grains produced are larger, they are damaged to a certain extent, resulting in lower light response. However, compared with Example 2, the response speed of the It characteristic curve in Example 3 is slower and the switching ratio is lower.
[0086] The present invention provides a method for preparing a NaSbS2 photoelectronic material film and an application example of a NiO / NaSbS2 heterojunction in photoelectric detection. A mixed solvent of ethylenediamine and β-mercaptoethanol was developed to dissolve sodium hydroxide, antimony oxide, and sublimed sulfur as a precursor solution for synthesizing NaSbS2, and a pure cubic NaSbS2 film with a band gap of 1.70 eV was grown by solution spin coating. The morphology of the NaSbS2 film was optimized by adjusting the film forming temperature (Example 2) and the number of annealing times (Example 3) of NaSbS2. According to Example 1, a 0.5 μm large grain and uniform film morphology was obtained, and the preparation process of the film was simple, and the raw materials and preparation costs were low. By constructing a heterojunction film of NaSbS2 and NiO and a photoelectric detection device, excellent self-powered photoelectric detection performance was exhibited, wherein the dark current was only 8.42×10 -4 A.cm -2 Therefore, the above results provide technical references and application examples for the thin film preparation of NaSbS2 and ternary sulfide optoelectronic materials, their heterostructure construction and innovative applications in semiconductor functional devices.
[0087] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A NaSbS2 thin film material, which is prepared by dissolving sodium hydroxide, antimony oxide and sublimed sulfur in a mixed solvent of ethylenediamine and β-mercaptoethanol, and reacting at 50-70°C to obtain a NaSbS2 precursor solution, and then growing a pure phase cubic structure NaSbS2 thin film material on a NiO substrate by solution spin coating and annealing; the annealing temperature is 350-500°C; the volume ratio of ethylenediamine and β-mercaptoethanol is (2-3): (0.4-0.8); the mass ratio of sodium hydroxide, antimony oxide and sublimed sulfur is (0.05-0.06): (0.12-0.15): (0.15-0.18).
2. A NiO / NaSbS2 heterojunction thin film, which is a heterojunction formed by the NaSbS2 thin film material according to claim 1 and a NiO thin film.
3. A method for preparing a NiO / NaSbS2 heterojunction film as claimed in claim 2, which comprises using a magnetron sputtering device to sputter a layer of NiO film on an ITO substrate to obtain ITO / NiO; then spin-coating a NaSbS2 precursor solution on the ITO / NiO and annealing to obtain a NiO / NaSbS2 heterojunction film.
4. Use of the NiO / NaSbS2 heterojunction film according to claim 2 or the NiO / NaSbS2 heterojunction film obtained by the preparation method according to claim 3 in a semiconductor functional device, wherein the semiconductor functional device is a photodetector, a solar cell or a photoelectric memory.
5. The use according to claim 4, characterized in that The NiO / NaSbS2 heterojunction film is used in a photoelectric detector, which is composed of an ITO substrate layer, a NiO / NaSbS2 heterojunction film layer and an aluminum metal electrode.
6. The use according to claim 5, characterized in that Steps using the following method: Step 1: Sputtering NiO film The cleaned ITO substrate was placed in a magnetron sputtering apparatus, and NiO was sputtered onto the ITO substrate in an argon atmosphere for 23-28 minutes to create ITO / NiO; Step 2: Prepare NaSbS2 precursor solution Weigh sodium hydroxide, antimony oxide and sublimed sulfur into a beaker, add ethylenediamine and β-mercaptoethanol to form a mixed solution, and stir the mixed solution in an oil bath at 60°C until it is completely dissolved to form a yellow solution; Step 3: Preparation of NaSbS2 thin film In a glove box filled with nitrogen, ITO / NiO was placed on a coating machine, and the prepared NaSbS2 precursor solution was spin-coated on ITO / NiO and annealed and cooled. This process was repeated three times to obtain an ITO / NiO / NaSbS2 composite laminate film. Step 4: Electrode plating A layer of aluminum electrode with a thickness of 80-120 nm is coated on the surface of the ITO / NiO / NaSbS2 composite laminate film by a thermal evaporation coating apparatus.
7. The use according to claim 6, characterized in that In step 3, the coating machine was accelerated to 2000 rpm at an acceleration of 500 rad / s, rotated for 20 s, annealed on a hot stage at 450°C for 5 min, cooled for 3 min, and repeated 3 times.
Citation Information
Patent Citations
Sulfo sodium antimonite nano material preparation method
CN109437298A
Method for conveniently and efficiently preparing NaSbS2
CN110155960A
Ultraviolet detector based on NiO / beta-Ga2O3 heterojunction and preparation method thereof
CN110729376A